TELLING HADITH IN ITS MEANING AND ITS IMPACT ON THE ATTITUDE OF THE ARABIC LANGUAGE SCHOLARS IN THE INFERENCE OF THE PROPHETIC HADITH - NASRI, SALIM (Journal of Social Sciences and Humanities, 2021)
The question of inference with the prophetic hadiths on proving arabic language grammar is an important affaire in which researchers' effort continue to widen the scope of research and study to determinate the position of grammarians and arabic language scholars, especially the advanced of them. the telling of hadith with sens comprehension that justify to some contemporary modernists keep away of the arabic language scholars from protesting with hadith in arabic language and its rulers, and this is what requires to stand on all opinions and show them up.